Annual population dynamics of mango fruit flies (Diptera: Tephritidae) in West Africa: socio-economic aspects, host phenology and implications for management. (25th April 2014) - Vayssières, Jean-François; Sinzogan, Antonio; Adandonon, Appolinaire; Rey, Jean-Yves; Dieng, Elhadj Oumar; Camara, Koumandian; Sangaré, Morodian; Ouedraogo, Sylvain; Hala, N'klo; Sidibé, Adama; Keita, Youssouf; Gogovor, Guy; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction. Losses in West African commercial mango orchards due to fruit fly infestations have exceeded 50% by the middle of the crop season since 2005, resulting in considerable income loss for the growers. Materials and methods. In 2009, weekly monitoring of adult fruit fly species of economic significance was carried out in eight West African countries at 12 sites across five agro-ecological zones: (i) Humid Forest, (ii) Guinean savanna, (iii) Southern Sudan, (iv) Northern Sudan, and (v) Sahelian. Trapping was performed using methyl eugenol and terpinyl acetate in 288 Tephri-traps, targeting Bactrocera invadens and Ceratitis cosyra. Results. The data showed that B. invadens was present throughout the year in the Forest zone, abundant for 7 months, with a peak in May at the end of the mango season, C. cosyra being totally absent. In the Guinean savanna zone, B. invadens was abundant for 6-7 months, with a peak at the beginning of June coinciding with the season, with a few C. cosyra. In the Southern Sudan zone, B. invadens was abundant for 6 months, with a peak in mid-June during the season, C. cosyra peaking in April. In the Northern Sudan zone, B. invadens was abundant for 5 months, with a peak at the end of June at the end of the season, C. cosyra peaking in May. In the Sahelian zone, B. invadens was abundant for 4 months, peaking in August during the season, C. cosyra peaking just before. These preliminary results showed that the exotic species, B. invadens, was present at high levels [mean peak of 378 flies per trap per day (FTD)] in all agro-ecological zones, while the native species, C. cosyra, preferred the drier zones of West Africa, with lower population levels (mean peak of 77 FTD). Conclusion. Detection trapping of male flies with parapheromones is a useful indicator of field population levels and could be used to deploy control measures (IPM package) in a timely manner when the Economic Injury Level is reached. Control strategies for these quarantine mango fruit fly species are discussed with respect to agro-ecological zones and the phenological stages of the mango tree.